Pengaruh Berbagai Komposisi Bokashi Ampas Biji Kakao Dan Pemberian Em4 Yang Berbeda Terhadap Pertumbuhan Dan Produksi Tanaman Petsai (Brassica chinensis L.) - N Riry; Herman Rehatta; V. L Tanasale (Faculty of Agriculture, Pattimura University, 2013)
Lettuce vegetable has high economic value and have a good prospect to increase famers income. Bokashi is organic fertiliser that can be used to increase the plant growth and production. The purpose of research were to investigate the influence of all sorts of bokashi composition of composted cocoa kernel and different doses of EM4 on the growth and production of lettuce. The research materials were lettuce germ that have attained the age of two weeks. The treatments were statistically designed with two factors and three repetitions. The treatments consisted of without bokashi (B0/control), B1=25 %, B2=50 %, B3=75 %, B4=100 % and EM4 (E0=control), E1=5ml/l water, E2=10ml/l water, E3=15ml/l water. The result showed that bokashi influenced significantly on the growth of lettuce. Level of bokashi 100 % was the best treatment, as measured from the height of the plant growth, leaf wide, fresh weight of crown and fresh weight of root, while the number of leaf was better at treatment of bokashi level 75 %.